If $\alpha $ and $\beta $ are the solutions of the equation $a\tan \theta + b\sec \theta = c$, then show that$\tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {c^{^2}})}}$.
Answer
Verified
507.3k+ views
Hint: Here, we will use the trigonometric formulae and roots of quadratic equation formulas.
Given,
$a\tan \theta + b\sec \theta = c \to (1)$
Now, equation (1) can be written as
$ \Rightarrow b\sec \theta = c - a\tan \theta $
Squaring the equation on both sides, we get
$\begin{gathered}
\Rightarrow {b^2}{\sec ^2}\theta = {(c - a\tan \theta )^2} \\
\Rightarrow {b^2} (1 + {\tan ^2}\theta ) = {c^2} + {a^2}{\tan ^2}\theta - 2ac\tan \theta [\because {\sec ^2}\theta = 1 + {\tan ^2}\theta ] \\
\Rightarrow ({a^2} - {b^2}){\tan ^2}\theta - 2ac\tan \theta + ({c^2} - {b^2}) = 0 \to (2) \\
\end{gathered} $
As, we can see equation (2) is in the form of quadratic equation of $\tan \theta $.Now, let $\tan \alpha $ and $\tan \beta $ be the roots of equation (2) (since, $\alpha $ and $\beta $ are roots of the equation).Therefore, we can apply the sum of roots and product of roots formula such that we get
$\tan \alpha + \tan \beta = \dfrac{{2ac}}{{({a^2} - {b^2})}} \to (3)[\because $Sum of the roots =$\dfrac{{{\text{ - coefficient of x}}}}{{{\text{coefficient of}}{{\text{x}}^{\text{2}}}}}$]
$\tan \alpha \tan \beta = \dfrac{{({c^2} - {b^2})}}{{({a^2} - {b^2})}} \to (4)[\because $Product of the roots =$\dfrac{{{\text{coefficient constant}}}}{{{\text{coefficient of}}{{\text{x}}^{\text{2}}}}}$]
Now, we need to find \[\tan (\alpha + \beta )\], we know that
\[\tan (\alpha + \beta ) = \dfrac{{\tan \alpha + \tan \beta }}{{1 - \tan \alpha .\tan \beta }} \to (5)\].
So, substituting equation (3) and (4) in equation (5), we get
\[\begin{gathered}
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{\tan \alpha + \tan \beta }}{{1 - \tan \alpha .\tan \beta }} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{\dfrac{{2ac}}{{({a^2} - {b^2})}}}}{{1 - (\dfrac{{({c^2} - {b^2})}}{{({a^2} - {b^2})}})}} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {b^2}) - ({c^2} - {b^2})}} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {c^{^2}})}} \\
\end{gathered} \]
Hence, we proved that $\tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {c^{^2}})}}$.
Note: Here, we need to convert the given equation in form of $\tan \theta $ such that we can use $\tan \alpha $ and $\tan \beta $ as the roots of the equation to find $\tan (\alpha + \beta )$.
Given,
$a\tan \theta + b\sec \theta = c \to (1)$
Now, equation (1) can be written as
$ \Rightarrow b\sec \theta = c - a\tan \theta $
Squaring the equation on both sides, we get
$\begin{gathered}
\Rightarrow {b^2}{\sec ^2}\theta = {(c - a\tan \theta )^2} \\
\Rightarrow {b^2} (1 + {\tan ^2}\theta ) = {c^2} + {a^2}{\tan ^2}\theta - 2ac\tan \theta [\because {\sec ^2}\theta = 1 + {\tan ^2}\theta ] \\
\Rightarrow ({a^2} - {b^2}){\tan ^2}\theta - 2ac\tan \theta + ({c^2} - {b^2}) = 0 \to (2) \\
\end{gathered} $
As, we can see equation (2) is in the form of quadratic equation of $\tan \theta $.Now, let $\tan \alpha $ and $\tan \beta $ be the roots of equation (2) (since, $\alpha $ and $\beta $ are roots of the equation).Therefore, we can apply the sum of roots and product of roots formula such that we get
$\tan \alpha + \tan \beta = \dfrac{{2ac}}{{({a^2} - {b^2})}} \to (3)[\because $Sum of the roots =$\dfrac{{{\text{ - coefficient of x}}}}{{{\text{coefficient of}}{{\text{x}}^{\text{2}}}}}$]
$\tan \alpha \tan \beta = \dfrac{{({c^2} - {b^2})}}{{({a^2} - {b^2})}} \to (4)[\because $Product of the roots =$\dfrac{{{\text{coefficient constant}}}}{{{\text{coefficient of}}{{\text{x}}^{\text{2}}}}}$]
Now, we need to find \[\tan (\alpha + \beta )\], we know that
\[\tan (\alpha + \beta ) = \dfrac{{\tan \alpha + \tan \beta }}{{1 - \tan \alpha .\tan \beta }} \to (5)\].
So, substituting equation (3) and (4) in equation (5), we get
\[\begin{gathered}
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{\tan \alpha + \tan \beta }}{{1 - \tan \alpha .\tan \beta }} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{\dfrac{{2ac}}{{({a^2} - {b^2})}}}}{{1 - (\dfrac{{({c^2} - {b^2})}}{{({a^2} - {b^2})}})}} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {b^2}) - ({c^2} - {b^2})}} \\
\Rightarrow \tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {c^{^2}})}} \\
\end{gathered} \]
Hence, we proved that $\tan (\alpha + \beta ) = \dfrac{{2ac}}{{({a^2} - {c^{^2}})}}$.
Note: Here, we need to convert the given equation in form of $\tan \theta $ such that we can use $\tan \alpha $ and $\tan \beta $ as the roots of the equation to find $\tan (\alpha + \beta )$.
Recently Updated Pages
Class 10 Question and Answer - Your Ultimate Solutions Guide
Master Class 10 General Knowledge: Engaging Questions & Answers for Success
Master Class 10 Computer Science: Engaging Questions & Answers for Success
Master Class 10 Science: Engaging Questions & Answers for Success
Master Class 10 Social Science: Engaging Questions & Answers for Success
Master Class 10 Maths: Engaging Questions & Answers for Success
Trending doubts
Assertion The planet Neptune appears blue in colour class 10 social science CBSE
The term disaster is derived from language AGreek BArabic class 10 social science CBSE
What is Commercial Farming ? What are its types ? Explain them with Examples
Imagine that you have the opportunity to interview class 10 english CBSE
Find the area of the minor segment of a circle of radius class 10 maths CBSE
Differentiate between natural and artificial ecosy class 10 biology CBSE